A study of nasal carriage of methicillin-resistant staphylococcus aureus in patients undergoing hemodialysis in a tertiary care hospital of Punjab - Dhillon, Prabhjot Singh; Sharma, Vishal; Brar, Manpreet Kaur; Thakur, Durgesh; Rishu, Rupali; ., Rishu; Kansal, Rinkal (International Journal Of Community Medicine And Public Health, 2021)
Background: Infection is one of the major problems encountered in hemodialysis patients. The mortality rate among the patients undergoing hemodialysis remains unsatisfactorily high. Hemodialysis patients have higher nasal carriage rate of Staphylococcus aureus than the healthy population. In long-term hemodialysis patients, colonization is a significant problem and is associated with an increased risk of the bloodstream infections. The antimicrobial resistance to this pathogen is increasing rapidly, and the consequences of methicillin resistance for the outcomes of Staphylococcus aureus infections are drastic. Methods: Two swabs were collected from anterior nares of patients undergoing hemodialysis, and then these swabs were transferred to microbiology laboratory for processing. Isolated strains were subjected to antimicrobial susceptibility testing using Kirby-Bauer disc diffusion. Methicillin resistance was detected by using cefoxitin disc. Inhibition zone diameters were measured as per CLSI criteria. Vancomycin screen agar test was done. Brain heart infusion agar plates containing 6 µg/ml of vancomycin were used. S. aureus ATCC 29213 was used as reference strain. Results: It was observed that 38% (38/100) of the hemodialysis patients were carriers of S. aureus followed by CoNS, followed by aerobic spore bearers. All the S. aureus isolates (100%, 38/38) were methicillin-resistant (MRSA). Conclusions: Staphylococcal nasal carrier status in hemodialysis patients along with antibiotic susceptibility testing should be done in routine and infection control practices should be followed to prevent the transmission of MRSA among chronic hemodialysis patients.